Neonatal admission and its relationship to maternal pain: Pain scores and analgesia - Cooper, Alannah; Brown, Janie; Kelly, S.; Eccles, S.P.; Parsons, R.; Osseiran-Moisson, Rebecca (LIPPINCOTT WILLIAMS & WILKINS, 2020)
The aim of this study was to determine whether postnatal women whose babies required neonatal intensive care unit (NICU) admission self-reported lower pain scores and required less analgesia than women whose babies remained with them. A prospective matched audit comparing pain scores and analgesia requirements where every woman with a baby admitted to the NICU was matched to 2 women whose babies remained on the ward was undertaken. Matches were based on age, number of previous births, type of birth, episiotomy, and epidural or spinal analgesia use. Data were collected on pain scores and analgesia administered in the first 72 hours postbirth. A total of 150 women were recruited and matched from November 2015 to May 2017. No statistically significant differences were found between the 2 groups for opiate analgesia use (P =.91) or pain scores (P =.89). Regardless of NICU admission, significantly higher pain scores were reported in participants who had episiotomies (P =.03). Birth via cesarean birth resulted in significantly higher pain scores (P <.01) and greater opiate administration (P <.01). This study found no statistically significant difference between pain scores or analgesia use of mothers whose babies required NICU admission and mothers whose babies remained with them.